Keys to female athlete performance in Paris 2024 - Boz, E.; Adatepe, E.; Çelik, H.; Kirkbir, H.; Öktem, T.; Ünlü, Y.; Öz, Ü.; Yilmaz, B. (Frontiers in Psychology, 2026)
The research was conducted to identify the key factors influencing the performance of Turkish female athletes participating in the Paris 2024 Olympic Games. In this context, seven female Olympic athletes who participated in the relevant organization volunteered to take part in the research. A semi-structured interview form prepared by the researchers was used to identify the participants` views on the factors affecting their performance. Individual interviews were conducted with each participant at different times, and all interviews were recorded. All interview transcripts obtained were analyzed and visualized using MAXQDA 2020 software. In the study, the experiences of female athletes were grouped under five themes: factors most affecting performance, environmental factors, physiological factors, socio-cultural factors, and psychological factors. The findings show that the athletes` experiences are not limited to athletic performance alone, but are also influenced by multidimensional factors such as organizational shortcomings, environmental conditions, psychological pressure, socio-cultural interactions, and physiological conditions. In the study, first-time participants were positively influenced by motivation, team support, and communication with foreign athletes, while experienced athletes, having higher expectations, criticized factors such as organizational shortcomings, hygiene, and nutrition issues. The study reveals that the factors affecting the performance of female athletes are multidimensional and interactive, emphasizing the importance of comprehensively considering physiological, psychological, environmental, and socio-cultural needs in the planning of international sports organizations. In particular, strengthening health support, nutrition services, cultural adaptation, and social support mechanisms are recommended as measures that will increase athletes` performance and experience satisfaction.